Capilliposide C from Lysimachia capillipes Restores Radiosensitivity in Ionizing Radiation-Resistant Lung Cancer Cells Through Regulation of ERRFI1/EGFR/STAT3 Signaling Pathway - Wu, Kan; Chen, Xueqin; Feng, Jianguo; Zhang, Shirong; Xu, Yasi; Zhang, Jingjing; Wu, Qiong; You, Mingliang; Xia, Bing; Ma, Shenglin (Frontiers in Oncology, 2021)
Aims Radiation therapy is used as the primary treatment for lung cancer. Unfortunately, radiation resistance remains to be the major clinic problem for lung cancer patients. Lysimachia capillipes capilliposide C (LC-C), an extract from LC Hemsl, has demonstrated multiple anti-cancer effects in several types of cancer. Here, we investigated the potential therapeutic impacts of LC-C on radiosensitivity in lung cancer cells and their underlying mechanisms. Methods Non-small cell lung cancer cell lines were initially irradiated to generate ionizing radiation (IR)-resistant lung cancer cell lines. RNA-seq analysis was used to examine the whole-transcriptome alteration in IR-resistant lung cancer cells treated with or without LC-C, and the differentially expressed genes with most significance were verified by RT-qPCR. Colony formation assays were performed to determine the effect of LC-C and the target gene ErbB receptor feedback inhibitor 1 (ERRFI1) on radiosensitivity of IR-resistant lung cancer cells. In addition, effects of ERRFI1 on cell cycle distribution, DNA damage repair activity were assessed by flow cytometry and γ-H2AX immunofluorescence staining respectively. Western blotting was performed to identify the activation of related signaling pathways. Tumor xenograft experiments were conducted to observe the effect of LC-C and ERRFI1 on radiosensitivity of IR-resistant lung cancer cells in vivo. Results Compared with parental cells, IR-resistant lung cancer cells were more resistant to radiation. LC-C significantly enhanced the effect of radiation in IR-resistant lung cancer cells both in vitro and in vivo and validated ERRFI1 as a candidate downstream gene by RNA-seq. Forced expression of ERRFI1 alone could significantly increase the radiosensitivity of IR-resistant lung cancer cells, while silencing of ERRFI1 attenuated the radiosensitizing function of LC-C. Accordingly, LC-C and ERRFI1 effectively inhibited IR-induced DNA damage repair, and ERRFI1 significantly induced G2/M checkpoint arrest. Additional investigations revealed that down-regulation of EGFR/STAT3 pathway played an important role in radiosensitization between ERRFI1 and LC-C. Furthermore, the high expression level of ERRFI1 was associated with high overall survival rates in lung cancer patients. Conclusions Treatment of LC-C may serve as a promising therapeutic strategy to overcome the radiation resistance and ERRFI1 may be a potential therapeutic target in NSCLC.